Thermostability and functionality evaluation of laccases from Pleurotus ostreatus and Pycnoporus cinnabarinus: An In-silico assay: Biochemical properties of laccases from fungi in silico method - Mohtashami, Mahnaz; Taghavizadeh Yazdi, Mohammad Ehsan; Gholampour-Faroji, Nazanin; Ghasemi, Ahmad; Haddad-Mashadrizeh, Aliakbar (Iranian Journal of Pharmaceutical Sciences, 2023)
Laccase enzymes are widely used in industrials and therefore achievement to the resources of this enzyme with high thermostability is obligatory. Accordingly, a deeper investigation for understanding the structure and function of PoxA1b from Pleurotus ostreatus, as a fungal enzyme with the possible desired conditions, was accomplished by using in-silico methods. Our study led to modeling a tertiary structure of the enzyme with 72% identity to the laccase from Trametes sp. AH28-2, with high quality. Moreover, structural stability of modeled enzyme compared to laccase from Pycnoporus cinnabarinus (LPC), were proved during 20 ns at 300 and 333K. Interestingly, this data showed that the modeled enzyme is more stable than LPC at 333 K. On the other hand, interaction assay of PoxA1b and LPC with benzo[a]pyrene (BaP), as a Polycyclic aromatic hydrocarbons (PAHs), revealed suitable affinity for both of them with -9.1 and -8.8 of binding energy, respectively. Taken together, these data show that both laccase from Pleurotus ostreatus and Pycnoporus cinnabarinus are stable until 60 °C with suitable affinity to substrate. Bearing in mind, PoxA1b is a favorable candidate for industrial and environmental applications, especially in PAH detoxification.